Two Chloroplast Proteins Suppress Drought Resistance by Affecting ROS Production in Guard Cells. Issue 4 (15th October 2016) - Wang, Zhen; Wang, Fuxing; Hong, Yechun; Huang, Jirong; Shi, Huazhong; Zhu, Jian-Kang
Abstract : Suppressing chloroplastic HCF106 and THF1 expression enhances drought resistance in Arabidopsis. Abstract: Chloroplast as the site for photosynthesis is an essential organelle in plants, but little is known about its role in stomatal regulation and drought resistance. In this study, we show that two chloroplastic proteins essential for thylakoid formation negatively regulate drought resistance in Arabidopsis ( Arabidopsis thaliana ). By screening a mutant pool with T-DNA insertions in nuclear genes encoding chloroplastic proteins, we identified an HCF106 knockdown mutant exhibiting increased resistance to drought stress. The hcf106 mutant displayed elevated levels of reactive oxygen species (ROS ) in guard cells, improved stomatal closure, and reduced water loss under drought conditions. The HCF106 protein was found to physically interact with THF1, a previously identified chloroplastic protein crucial for thylakoid formation. The thf1 mutant phenotypically resembled the hcf106 mutant and displayed more ROS accumulation in guard cells, increased stomatal closure, reduced water loss, and drought resistant phenotypes compared to the wild type. The hcf106thf1 double mutant behaved similarly as the thf1 single mutant. These results suggest that HCF106 and THF1 form a complex to modulate chloroplast function and that the complex is important for ROS production in guard cells and stomatal control in response to environmental stresses. Our results also suggest that modulating chloroplastic proteins could be a way for improving drought resistance in crops.